Nanoparticle elasticity regulates phagocytosis and cancer cell uptake - Hui, Yue (2020)
The ability of cells to sense external mechanical cues is essential for their adaptation to the surrounding microenvironment. However, how nanoparticle mechanical properties affect cell-nanoparticle interactions remains largely unknown. Here, we synthesized a library of silica nanocapsules (SNCs) with a wide range of elasticity (Young’s modulus ranging from 560 kPa to 1.18 GPa), demonstrating the impact of SNC elasticity on SNC interactions with cells. Transmission electron microscopy revealed that the stiff SNCs remained spherical during cellular uptake. The soft SNCs, however, were deformed by forces originating from the specific ligand-receptor interaction and membrane wrapping, which reduced their cellular binding and endocytosis rate. This work demonstrates the crucial role of the elasticity of nanoparticles in modulating their macrophage uptake and receptor-mediated cancer cell uptake, which may shed light on the design of drug delivery vectors with higher efficiency.